Effect of Corporate Environmental Performance on Banks’ Loan Pricing - Siwela, Witness; Ngwakwe, Collins C. (International Journal of Economics and Financial Issues, 2024)
Capital lenders of money such as banks are perceived to be environmentally sensitive in contemporary times. This sensitivity is evidenced by the advent of new concepts such as green financing in the context of environmental catastrophes which are exacerbated by the climate change crisis. Thus, financial institutions such as banks face a dilemma in deciding whether to prioritise sustainability financing or seek after profit maximisation. To this end, little is known if corporate environmental performance lures support of key stakeholders such as banks. The study renders empirical evidence on this phenomenon by investigating short run and long run dynamics between corporate environmental performance and banks’ loan pricing. Archival data were collected from the FTSE/JSE RII listed companies. A sample of 21 companies generated a short panel data set of six years per cross-section totalling 126 observations. The study adopted first differenced econometric models in statistical panel data analyses namely Panel Vector Error Correction Model (VECM), and subsequently Panel Least Squares (PLS), Wald Test, and Impulse Response Functions (IRF). Findings revealed a statistically significant positive impact, both in the short run and long run, between environmental performance predictors and banks’ loan pricing. While the study makes immense contribution to literature, it renders new assertions in understanding stakeholders’ current environmental practices and initiate a new agenda for future research.